Aplikasi Pembelajaran Linked List Berbasis Mobile Learning - Abdi Dharma; Hendra Handoko Syahputra P (RJOCS (Riau Journal of Computer Science), 2018)
Data structure is a subject that must be taken by a student in Informatics Engineering course. In the process of teaching and learning, students always have difficulty and confusion to study the course of data structures, especially the material Linked List. This is due to the complexity of the workings of the linked list itself. Learning media can be found through various media such as books, journals, e-books, computers, mobile learning, and others. With technology-based mobile learning, researchers are trying to design Linked List learning software. With this application is expected to help students to understand both the workings and processes of the Linked List itself using the model explicit instruction (direct learning). This application is designed as interactive as possible so that students do not feel bored in studying and understanding the material of Linked List. This application displays step by step formation of the Linked List itself and this material can be repeated by students either anywhere and anytime by using Android-based Smartphone.